2014
DOI: 10.1002/cbf.3072
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone, a PPARγ agonist, ameliorates palmitate‐induced insulin resistance and apoptosis in skeletal muscle cells

Abstract: Saturated free fatty acids (FFAs), such as palmitate, have been shown to induce cellular apoptosis. Strategies for preventing the cytotoxic effect of palmitate are useful in reduction of diabetes complications. In this study, we introduced RSG as an agent that protects skeletal muscle cells against palmitate-induced apoptosis and insulin resistance. It appears that RSG protects skeletal muscle cells against palmitate-induced apoptosis via the PPARγ-dependent and PTP1B-independent mechanisms. Given the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…Because previous studies have reported that palmitate induces apoptosis in various cell types [16][17][18], we first determined the appropriate dose of palmitate for inducing apoptosis in HepG2 cells. The results of the MTT assay revealed that lower than 0.5mM of palmitate did not significantly suppressed the viability of HepG2 cells (Fig.…”
Section: Palmitate Decreases Cell Viability and Induces Apoptosis In mentioning
confidence: 99%
“…Because previous studies have reported that palmitate induces apoptosis in various cell types [16][17][18], we first determined the appropriate dose of palmitate for inducing apoptosis in HepG2 cells. The results of the MTT assay revealed that lower than 0.5mM of palmitate did not significantly suppressed the viability of HepG2 cells (Fig.…”
Section: Palmitate Decreases Cell Viability and Induces Apoptosis In mentioning
confidence: 99%
“…These changes suggest that PPARγ upregulation of SCD-1 resulted in elevated lipogenesis and strengthened adiponectin signaling. Further studies indicated that PPARγ agonists weaken palmitate-induced endoplasmic reticulum stress and apoptosis by SCD-1 generation (8082). SCD-1 upregulation may lead to the lessening of cardiovascular disturbances through therapy with PPARγ agonists (81).…”
Section: Discussionmentioning
confidence: 99%
“…These conditions are detrimental for cellular function and may eventually lead to cell death. Apoptosis has been shown to occur in skeletal muscle cells exposed to saturated palmitic acid [4,5]. Although various mechanisms may be involved, changes in mitochondrial respiration seem to play a central role in FFA-induced cellular damage (reviewed Abstract Unsaturated free fatty acids (FFA) are able to prevent deleterious effects of saturated FFA in skeletal muscle cells although the mechanisms involved are still not completely understood.…”
Section: Introductionmentioning
confidence: 99%